A new recycling strategy for preparing flame retardants from polyphenylene sulfide waste textiles. (October 2021) - Wang, Hao; Zhu, Zongmin; Yuan, Jun; Wang, Hua; Wang, Zhaojia; Yang, Feihua; Zhan, Jiayu; Wang, Luoxin
Abstract: In this paper, the waste polyphenylene sulfide (PPS) filter bag was converted to waste PPS powder through thermal aging, ball milling and screening, and firstly used as flame retardant to improve the flame retardance of epoxy resin (EP). TG results presented that, it started to decompose at 510.6 °C with 62.08% of residue mass at 800 °C, which showed good charring ability. The UL-94 and cone calorimeter tests showed that waste PPS not only improved the flame retardance of EP but also largely decreased heat and smoke/toxic gases release. Adding 15 wt% waste PPS made EP composites acquire a UL-94 V-1 rating and resulted in a 42.24% reduction in the peak of heat release rate (PHRR). What' more, the peak of smoke production rate (PSPR) and peak of CO production (PCOP) declined by 27.27% and 45.16%. The morphology of char residue was also observed by scanning electron microscope (SEM), and it was concluded that, introduction of waste PPS indeed improved the compact of char layer, which was be responsible for enhancement in flame retardance. This work provided a new way and theoretical basis for realizing high value recycling of PPS solid waste. Graphical abstract: Image 1 Highlights: Waste polyphenylene sulfide (PPS) filter bag was firstly used as flame retardant for polymer. The components of the prepared waste PPS powder were characterized by FTIR, XPS and XRD. The waste PPS simultaneously enhanced flame retardance and smoke suppression properties of epoxy resin.